Characteristics of primary glomerular disease patients with hematuria in Turkey: The data from TSN-Gold working group - Şumnu, Abdullah; Türkmen, Kültigin; Cebeci, Egemen; Türkmen, Aydın; Eren, Necmi; Seyahi, Nurhan; Oruç, Ayşegül; Dede, Fatih; Derici, Ülver; Baştürk, Taner; Şahin, Garip; Sipahioğlu, Murat; et al. (Oxford University Press, 2020)
[Abstract Not Available]
Keywords: TSN-Gold; Hematuria; Glomerular Disease